2012
DOI: 10.1089/scd.2011.0348
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood-Derived Stromal Cells Are Superior to Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells in Inducing Myeloid Lineage Differentiation In Vitro

Abstract: Stromal cells and mesenchymal stem cells (MSCs), 2 important cell populations within the hematopoietic microenvironment, may play an important role in the development of hematopoietic stem/progenitor cells. We have successfully cultured human umbilical cord blood-derived stromal cells (hUCBDSCs). It has been demonstrated that MSCs also exist in hUCB. However, we have not found any reports on the distinct characteristics of hUCBDSCs and human umbilical cord blood-derived mesenchymal stem cells (hUCBDMSCs). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Arthur et al (29) reported that Twist-1-overexpressing BMSCs exhibited an enhanced capacity in maintaining human CD34 + hematopoietic stem cells (HSCs) in long-term culture-initiating cell (LTC-IC) assays. It was also confirmed that MSCs support the proliferation of hematopoietic stem/progenitor cells in vitro by coculture of human umbilical cord blood mononuclear cells and umbilical cord mesenchymal stem cells for 14 days (30). Few studies have demonstrated that ADSCs support the long-term proliferation of hematopoietic stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 77%
“…Arthur et al (29) reported that Twist-1-overexpressing BMSCs exhibited an enhanced capacity in maintaining human CD34 + hematopoietic stem cells (HSCs) in long-term culture-initiating cell (LTC-IC) assays. It was also confirmed that MSCs support the proliferation of hematopoietic stem/progenitor cells in vitro by coculture of human umbilical cord blood mononuclear cells and umbilical cord mesenchymal stem cells for 14 days (30). Few studies have demonstrated that ADSCs support the long-term proliferation of hematopoietic stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 77%
“…Yet, it is not clear why perivascular cells should abandon their niche and should be circulating in cord blood. In addition, cord blood was reported to give rise to distinct stromal populations in terms of morphology, isolation frequency, proliferation rate, differentiation potentialities, and surface markers [23][24][25][26].…”
mentioning
confidence: 99%
“…UCB has been shown to be abundant in hematopoietic growth factors, including G-CSF (16), GM-CSF (5), EPO (16), IL-2 (16), IL-6 (16,17), insulin-like growth factors (18) and steel factor (7). The expression levels of these growth factors are significantly higher in UCB compared with the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional allogeneic UCB-HSC transplantation requires partial human leukocyte antigen (HLA) matching, ablation of the recipient’s marrow and immunosuppression following transplantation (5,6). These requirements significantly limit the broad application of UCB-HSC transplantation in patients with chemotherapy-related myelosuppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation